Increasing Financial Literacy in RT RW net Indonesia Cooperatives and Msmes Through Simple Bookkeeping - Amelia Rahmi; Fredi Andria; Salmah Salmah (International Journal of Research in Community Services, 2023)
This Community Service activity aims to increase financial literacy in RT RW Net Indonesia Cooperatives and MSMEs in Tugubandung Village through simple bookkeeping training. The background of this activity is the phenomenon of cooperatives and MSMEs who have yet to realize the importance of simple bookkeeping and have yet to prepare financial reports. The method for implementing this community service activity is to provide training in preparing simple financial statements. The implication of this community service activity is to increase the knowledge and ability of Cooperative managers and MSMEs owners to present financial reports through simple bookkeeping. By keeping simple bookkeeping, Cooperatives and MSMEs can have competitiveness and strengthen the economic pillars in achieving sustainable economic development goals.